Focal Points - Maarten C.W. Janssen (Tinbergen Institute, 1997)
This paper gives an overview of the literature on focal points. It starts with reviewing Schelling's seminalbook The Strategy of Conflict.I then discuss the problems that have to be faced when incorporating thenotion of focal points in theory of games. Two recent approaches are discussed that deal with focalpoints. The eductive approach is static and concentrates on how players can use aymmetries in thedescriptions of strategies. The evolutive approach is dynamic and focuses in the adaptive behaviour ofplayers.
Keywords: 330; Spieltheorie; Theorie